Complications and Prevention in the Use of Central Venous Catheter: A Nursing Approach - Zerrizuela , Marcela Fabiana; Walter A. Lara , Walter A. (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Introduction: Hospital acquired infections represent a serious problem for healthcare systems, increasing morbidity, mortality and healthcare costs. According to the World Health Organization, up to 15% of patients in low- and middle-income countries contract infections during hospitalization, highlighting the need for preventive measures. Central Venous Catheters (CVC), although indispensable in the management of critically ill patients, are associated with infectious complications that constitute 14% of nosocomial infections, mainly bacteremia and sepsis. Development: CVCs are medical devices designed to administer substances directly into the bloodstream, being essential in treatments such as transfusions, parenteral nutrition and administration of irritant drugs. However, their use can generate mechanical, infectious and thrombotic complications. These complications are often associated with the lack of standardized protocols, inadequate biosafety practices and insufficient training of healthcare personnel. The review highlighted that infections are preventable through aseptic techniques, such as hand washing, use of sterile barriers, and proper cleaning of the insertion site and catheter connections. Conclusions: Successful prevention of complications associated with CVCs requires a multidisciplinary approach that includes ongoing staff training, implementation of evidence-based protocols, and use of monitoring tools such as checklists. These strategies not only ensure patient safety, but also reduce costs and improve clinical outcomes. The adoption of these practices is essential to optimize the quality of care in critically ill patients